2014
DOI: 10.1111/iej.12235
|View full text |Cite
|
Sign up to set email alerts
|

Clinical accuracy of two electronic apex locators in teeth with large periapical lesions

Abstract: Despite the presence of exudate in the root canals, the position of the major foramen in teeth with large periapical lesions can be determined with high level of precision either by ProPex or Apex Pointer. Both EALs can be used safely in working length determination of teeth with large periapical lesions, which have persistent intracanal exudate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 37 publications
0
3
0
2
Order By: Relevance
“…To measure accuracy of the EALs, +/-0.5 mm difference has been considered accurate in various studies (11,19,24,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…To measure accuracy of the EALs, +/-0.5 mm difference has been considered accurate in various studies (11,19,24,25,26).…”
Section: Resultsmentioning
confidence: 99%
“…Only very limited designs of clinical studies are available for assessing the accuracy of apex locators. Commonly used in vivo study designs evaluate the accuracy of EAL prior and after the extraction of periodontally‐weak teeth or teeth intended for orthodontic extraction, subjecting the patient to cone‐beam computed tomography (CBCT) or testing the EAL during apical surgery . Each study design has its own limitations in replicating the clinical scenario where the EAL are required to operate.…”
Section: Discussionmentioning
confidence: 99%
“…This posed some clinical concerns. The working length was initially confirmed with an electronic apex locator because Ç alişkan et al (39) have shown that electronic apex locators can be used with a high level of accuracy in canals with persistent intracanal exudate where teeth have had large periapical lesions. The canals were redressed primarily because the cone-beam imaging revealed the lesion had extended to involve the apices of the canine and first premolar teeth (Fig.…”
Section: Discussionmentioning
confidence: 99%